2018
DOI: 10.1039/c8gc01534a
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free oxidative cyclization of N-propargyl ynamides: stereospecific construction of linear polycyclic N-heterocycles

Abstract: An efficient NaBArF4-catalyzed oxidative cascade cyclization of N-propargyl ynamides has been developed, leading to a diverse range of polycyclic N-heterocycles with high diastereoselectivity and enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 91 publications
0
13
0
1
Order By: Relevance
“…According to the above experimental observations and previous studies, [6,7] a plausible reaction pathway to rationalize the formation of eight-membered lactam 2a is presented in Scheme 2. First, nucleophilic attack of N-oxide 3e occurs on the Zn-activated ynamide 1a to afford the vinyl zinc alkene intermediate B.…”
Section: Figurementioning
confidence: 53%
See 1 more Smart Citation
“…According to the above experimental observations and previous studies, [6,7] a plausible reaction pathway to rationalize the formation of eight-membered lactam 2a is presented in Scheme 2. First, nucleophilic attack of N-oxide 3e occurs on the Zn-activated ynamide 1a to afford the vinyl zinc alkene intermediate B.…”
Section: Figurementioning
confidence: 53%
“…And importantly, the unwanted overoxidation could be completely suppressed in this type of non-noble metal catalysis. As a result, this strategy has been widely utilized into the synthesis of a variety of five-and six-membered lactams [6] and α-functionalized amides (Scheme 1a). [7] Inspired by these results and our recent work on the catalytic construction of medium-sized lactams, [8] we envisioned that the synthesis of indole-fused medium-sized lactams might be achieved through non-noble metal-catalyzed ynamide oxidation/C-H functionalization of indoly ynamides (Scheme 1b).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Apart from indole, scope of simple aromatic substrates was also demonstrated (Scheme146). [168] In 2018, oxidation/Brønsted acid catalyzed cyclization of tryptamine-based ynamides 587 for the synthesis of 1H-pyrrolo[2,3-d]carbazole 588 derivatives was reported by Liu and Cheng. 10 mol %o fd iphenyl phosphate (DPP) in CH 2 Cl 2 at 0 8C was found to be optimum.…”
Section: Metamorphosis Of Heteroarene-tethered Ynamidesmentioning
confidence: 99%
“…In recent years, catalytic intermolecular diyne oxidation by an N-O bond oxidant [4] has attracted considerable interest as this chemistry offers great potential to build structurally complex cyclic molecules from readily available diynes. [5][6][7][8][9] For instance, Hashmi et al reported an elegant protocol for the gold-catalyzed oxidative diyne cyclization involving diyne oxidation, 1,6-carbene transfer, followed by Wagner−Meerwein chemistry, CH insertions or double oxidation. [5] Such a gold-catalyzed oxidative cyclization of diynes has been significantly advanced by Zhang, Ji, Ohno and Liu.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[8] Very recently, our group realized the relevant copper-and NaBAr F 4 -catalyzed oxidative cyclization of 1,5-diynes, allowing the divergent and practical synthesis of various valuable tricyclic N-heterocycles. [9] Inspired by these results and our recent study on the catalytic alkyne oxidations, [9,10] we envisioned that the preparation of synthetically useful γ-and δ-lactams might be achieved via catalytic oxidative cyclization of readily available 1,5-and 1,6-diynes. Herein, we report such an efficient NaBAr F 4 -catalyzed oxidative diyne cyclization, and importantly, this transition metal-free oxidative catalysis proceeds via a presumable Lewis acid-catalyzed S N 2' pathway, which is distinct from the relevant oxidative rhodium and gold catalysis (Scheme 1b).…”
Section: Background and Originality Contentmentioning
confidence: 99%